2016
DOI: 10.2495/sdp-v12-n3-446-456/010
|View full text |Cite
|
Sign up to set email alerts
|

Urban Facilities Management: A Systemic Process for Achieving Urban Sustainability

Abstract: With cities at the forefront of the challenge of achieving global sustainability, a key concern for urban management bodies is to identify ways to promote sustainable development at the urban and sub-urban level. Assessment mechanisms have dominated this field for the past two decades, and sustainable community assessment tools (SCATs) are fast becoming the principal framework adopted by urban planners and developers to drive sustainability. This paper investigates the efficacy and applicability of this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This is the goal for engaging in facilities management at the community level. Boyle and Michell (2017) examined the management issue in enabling sustainability in marginalized communities in South Africa. They found that urban services can be integrated with urban governance, so urban FM provides the integrated management of services for operations and sustainability of the urban environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the goal for engaging in facilities management at the community level. Boyle and Michell (2017) examined the management issue in enabling sustainability in marginalized communities in South Africa. They found that urban services can be integrated with urban governance, so urban FM provides the integrated management of services for operations and sustainability of the urban environment.…”
Section: Resultsmentioning
confidence: 99%
“…FM contributes at the strategic level by integrating the community and its facilities into the strategic plan of a city. The operational level is the operation of FM of public services for the well-being and health of those using the services (Boyle and Michell, 2017)). At the tactical level, the FM’s role is to ensure effective and efficient service delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban FM's efforts to improve the quality of the physical environment is its primary focus, whilst ensuring that there is an encompassing and holistic link between the citizens that live in this physical environment, as well as the services that support them (Salaj et al , 2020). Within the larger context of human activities in this area, using urban FM we can overcome the challenges posed when unsustainable human practices are a consequence of the way human activity is organised (Boyle and Michell, 2017, p. 449). Urban FM also has a place for fostering further innovation in this sector.…”
Section: Theoretical Approach and Definitionsmentioning
confidence: 99%